Carbon Dioxide, a Releaser for Digging Behavior in Solenopsis Geminata (Hymenoptera: Formicidae) - Walter Hangartner (Psyche: A Journal of Entomology)
The behavior of ants digging through sand or clay in the direction of trapped nestmates has been described by Belt (1874) and Lafleur (I940). Wilson (1958) showed that in Pogonomyrmex badius (Latreille) this behavior pattern is released by a volatile substance originating from the mandibular glands. Later, McGurk et al. (1966) identified the responsible compound as 4-methyl-3-heptanone. At the same time, Blum and Warter (1966) isolated 2-heptanone from Conomyrma pyramica (Roger) and described its function as the releaser of alarm and digging behavior. Spangler (1968) reported that not only whole workers, but also amputated parts as well as larvae and pupae of Pogonomyrmex occidentalis (Cresson) attract workers of this species and release digging behavior. Forrest (1963) studied Lasius flavus nearcticus and four species of Acanthomyops and found that workers also dig to free ants of another species but attack them as soon as they are released.